Experts versus novices: stiffness regulation during various stretch loads - Waldvogel, J.; Freyler, K.; Ringhof, S.; Ritzmann, R.; Gollhofer, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: High neuromuscular activity before and during ground contact (GC) are the prerequisites to benefit from energy saving mechanisms during stretch-shortening type actions (1). Especially time critical disciplines such as long jump (2) require immediate transition from eccentric to concentric muscle action (1). To meet such criteria athletes are highly involved in plyometric training. Therefore they have an exclusive neuromuscular control and stiffness regulation during the eccentric phase (3). During excessive stretch loads the eccentric activity is negatively affected possibly due to inhibitory influences (2,4). By directly comparing experts and novices the present study investigate the effect of expertise on the neuromuscular control and leg spring behavior in vertical jumps.